Pressureless sintering and gas flux properties of porous ceramic membranes for gas applications - David O. Obada; David Dodoo-Arhin; Muhammad Dauda; Fatai O. Anafi; Abdulkarim S. Ahmed; Olusegun A. Ajayi (Results in Physics, 2017)
The preparation and characterization of kaolin based ceramic membranes using styrofoam (STY) and sawdust (SD) as pore formers have been prepared by mechano-chemical synthesis using pressureless sintering technique with porogen content between (0–20) wt% by die pressing. Pellets were fired at 1150 °C and soaking time of 4 h. The membranes cast as circular disks were subjected to characterization studies to evaluate the effect of the sintering temperature and pore former content on porosity, density, water absorption and mechanical strength. Obtained membranes show effective porosity with maximum at about 43 and 47% respectively for membranes formulated with styrofoam and sawdust porogens but with a slightly low mechanical strength that does not exceed 19 MPa. The resultant ceramic bodies show a fine porous structure which is mainly caused by the volatilization of the porogens. The fabricated membrane exhibited high N2 gas flux, hence, these membranes can be considered as efficient for potential application for gas separation by reason of the results shown in the gas flux tests. Keywords: Porosity, Pore formers, Kaolin, Physico-mechanical properties, Gas separation, Gas flux